Encapsulamento de Trichoderma harzianum em matrizes à base de nanocelulose e carboximetilcelulose para aplicação na agricultura - Wolf, Mariana Govoni Brondi (Universidade Federal de São Carlos, 2023)
Microbial inoculants are a sustainable alternative to increase agricultural productivity and reduce environmental and health problems caused by the exacerbated use of agrochemicals. These bio-based products are formulations with living microorganisms that are able to increase the productivity of vegetal crops. Nevertheless, for the commercial success of these bioproducts, some challenges still need to be overcome, particularly those related to increasing the inoculant shelf life, and its protection during storage and after its application. In this sense, a suitable formulation plays a crucial role in the survival and efficacy of inoculants. For instance, encapsulating microorganisms in natural polymeric matrices has shown promising results in meeting the requirements for a good formulation. These materials have advantages such as biocompatibility, biodegradability, renewability and can be used as a nutrient source by microorganisms. In this context, although still underexplored for this type of application, the evaluation of cellulose-based materials, such as carboxymethyl cellulose or nanocellulose, may result in positive outcomes on increasing microbial inoculants protection. Therefore, the objective of this thesis was to assess the use of cellulose nanocrystals (CNC) and the CNC:carboxymethyl cellulose (CNC:CMC) composite for increasing the shelf-life and protection of the fungus Trichoderma harzianum, a well-known microbial inoculant mainly due to its effect as a biocontrol agent. To this end, dispersions of 5% (w/v) CNC and a 5% (w/v) CNC mixed with a 1.5% (w/v) CMC at a volumetric ratio of 3:1 (CNC:CMC), containing a spore concentration of 109 spores/g of polymers, were dripped to a crosslinking solution of CaCl2 (1 M). After coagulation, the viability of the microorganism was evaluated, and the produced beads were stored wet under refrigeration (4 °C). Characterizations such as X-ray microtomography and scanning electron microscopy (SEM) showed a good dispersion of the polymers in the encapsulating matrices, as well as the presence of the microorganism on the capsules’ surface. Shelf-life experiments highlighted that both matrices were able to reduce the mortality of encapsulated spores compared to the free microorganism (stored under the same conditions) after 9 and 12 months of storage. Additionally, the encapsulation increased the fungus protection when exposed to a temperature of 40 °C, a direct UV-C radiation, and during the contact with a commercial fungicide. Furthermore, after 1 year of storage, the biocontrol action of T. harzianum against the phytopathogen Fusarium solani remained preserved. Thus, the evaluated materials proved to be efficient in enhancing the protection of microbial inoculants, offering an interesting alternative for the formulation of these materials and for moving agriculture towards more sustainable practices aligned with the concepts of bioeconomy and climate change concerns.
Encapsulation of Trichoderma harzianum in nanocellulose and carboxymethyl cellulose based matrices for agricultural applications
Keywords: Nanocelulose; Carboximetilcelulose; Inoculantes microbianos; Encapsulamento; Tempo de prateleira; Trichoderma harzianum; Nanocellulose; Carboxymethylcellulose; Microbial inoculant; Encapsulation; Shelf-life; ENGENHARIAS::ENGENHARIA QUIMICA::PROCESSOS INDUSTRIAIS DE ENGENHARIA QUIMICA; ENGENHARIAS::ENGENHARIA QUIMICA